Pengaruh Pola Asuh Orang Tua terhadap Motivasi Belajar PAI Siswa Kelas III di SDN Kayumanis 01 Bogor - Lily Efriana Nasution; Muhyani Muhyani; Khaidir Fadil (Jurnal Dirosah Islamiyah, 2023)
This study aims to analyze the effect of parenting style on learning motivation of Islamic Religious Education (PAI) in class III students at SDN Kayumanis 01 Bogor. The parenting style adopted by parents has an important role in shaping children's learning motivation in PAI. This study uses a quantitative approach to the survei method. The research sample consisted of 70 grade III students who were randomly selected. The instrument used in this study was a previously validated questionnaire. The questionnaire was used to measure parenting styles and students' motivation to learn PAI. The validity and reliability of the collected data were analyzed using normality, homogeneity and simple linear regression tests to determine the influence between parenting styles and students' motivation to learn PAI. The results of the study showed that there was a positive relationship between parenting style and the motivation to learn PAI for third grade students at SDN Kayumanis 01 Bogor. Parents who provide emotional support and give gifts according to children's academic achievements tend to have children who are more motivated in learning PAI. In addition, parenting styles that emphasize wise direction and control also have a positive effect on students' motivation to learn PAI. This research contributes to the understanding of the importance of parenting in shaping the motivation to learn PAI in class III students. The practical implication of this research is the important role of parents in supporting and encouraging children's motivation to learn PAI. Schools and teachers can also play a role in providing guidance to parents regarding parenting styles that are effective in increasing students' motivation to learn PAI. Keywords: Parenting Patterns, Learning Motivation, Islamic Religious Education